New information on the chiropterofauna of Eastern Crimea - A. I. Ivanitzky; A. A. Maslov (Юг России: экология, развитие)
Aim. Study of the current state of the bat population of Eastern Crimea, features of distribution, occurrence and relative abundance of bats in the region, and monitoring of known colonies in underground cavities of the Kerch Peninsula.The results of original chiropterological studies in 2023–2024 in Eastern Crimea are presented. New data on 14 bat species were obtained from more than two dozen points in the region. A bat census was conducted in the shelters, primarily in the quarries of the Kerch Peninsula. A search for bat shelters in human buildings was also carried out. Animals were captured with mist nets. Our studies show that Nyctalus leisleri and Plecotus auritus, previously considered rare in the mountainous part of Eastern Crimea, are a common and widespread species here. The understanding of the distribution in the region has been significantly expanded for almost all 14 species.The data presented can be used both for fundamental research and for solving practical problems, primarily in the organisation and implementation of environmental measures.